2019
DOI: 10.1002/jcop.22254
|View full text |Cite
|
Sign up to set email alerts
|

Quality of collaboration within health promotion partnerships: Impact on sense of community, empowerment, and perceived projects' outcomes

Abstract: Community coalitions or intersectoral partnerships have long been advocated for the promotion of population health. In the present study, we assessed the quality of the functioning of health promotion partnerships created within a large community health promotion program implemented by the Emilia‐Romagna region located in the north‐east of Italy (2014–2016). In particular, we aimed to test the effectiveness of partnership working in strengthening participants' empowerment, sense of community and ultimately, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
0
19
1
1
Order By: Relevance
“…In line with theoretical arguments in the Community Experience Model (Boyd & Nowell, 2014; Boyd & Nowell, 2017; Nowell & Boyd, 2014), SOC‐R is more likely to have an indirect pattern of relationships to well‐being, while it is more likely to exhibit a stronger direct association to indices of participation and community engagement. By contrast, the present finding was not consistent with a recent study which demonstrated that SOC‐R did not have a significant effect on commitment to health promotion projects in the future (Cicognani, Albanesi, Valletta, & Prati, 2020). The authors concluded that SOC‐R may have a greater impact on commitment at the present time, while SOC might become more important for long‐term engagement.…”
Section: Summary and Concluding Discussioncontrasting
confidence: 99%
“…In line with theoretical arguments in the Community Experience Model (Boyd & Nowell, 2014; Boyd & Nowell, 2017; Nowell & Boyd, 2014), SOC‐R is more likely to have an indirect pattern of relationships to well‐being, while it is more likely to exhibit a stronger direct association to indices of participation and community engagement. By contrast, the present finding was not consistent with a recent study which demonstrated that SOC‐R did not have a significant effect on commitment to health promotion projects in the future (Cicognani, Albanesi, Valletta, & Prati, 2020). The authors concluded that SOC‐R may have a greater impact on commitment at the present time, while SOC might become more important for long‐term engagement.…”
Section: Summary and Concluding Discussioncontrasting
confidence: 99%
“…Further research attention should be paid to neighborhood social capital's multidimensionality. Using wave 2 of the National Social Life, Health, and Aging Project (NSHAP) survey, the same data set employed in the present study, York Cornwell and Cagney (2014) disaggregate the overall neighborhood social context (here referred to as "overall neighborhood social capital") into scales of social cohesion (a community's close-knittedness and trustingness, as well as congruence in values), social ties (how often community residents act in each other's interests), and danger (a community's extent of danger and crime; as explained in Section 2, this scale is here reverse coded to construct a measure of neighborhood safety), all of which impact residents' health (Cicognani et al, 2020; Gattino et al, 2013;Henderson et al, 2016;Kim & Ross, 2009;Weisburd et al, 2018). As well as some disagreement in the scholarly literature concerning whether troubled neighborhood conditions strengthen or weaken community social fabric, there is a dearth of research investigating how residents' health and well-being (e.g., Gariepy et al, 2014;Glymour et al, 2010;Wight et al, 2013), and different dimensions of neighborhood social capital change as neighborhood socioeconomic conditions change.…”
Section: Introductionmentioning
confidence: 99%
“…Os sentimentos de insegurança impactam negativamente o trabalho dos profissionais e têm consequências para a saúde do trabalhador e para a manutenção da disciplina e organização destes centros. Por outro lado, trabalhos comunitários que priorizam o apoio, a autoeficácia e o empoderamento, são capazes de criar um clima de segurança com consequências positivas para a saúde e para o futuro dos participantes (Cicognani et al, 2020).…”
Section: Discussionunclassified